PELATIHAN PENYUSUNAN RPP BERBASIS ETNOPEDAGOGI DI SD N 10 PEMECUTAN - I Komang Widana Putra; Ni Luh Sukanadi; I Komang Asmara Putra; Pramesti Artayani; Anggie Angellina Putri (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
The learning activities carried out every day meet the standards and are in accordance with the curriculum implemented at the school. PSP Indonesian Language and Literature, Faculty of Teacher Training and Education, Univercity of Mahasaraswati Denpasar carries out community service at SD Negeri 10 Pemecutan Kelod. One of the topics discussed was Ethnopedagogy-Based RPP Preparation Training. This service aims to emphasize local wisdom and build behavior and attitudes that are integrative with local cultural values. In fact, there are still teachers at SD Negeri 10 Pemecutan who don’t understand how to prepare lesson plans based on local wisdom. During daily learning, teachers have included or applied local wisdom but it has not been written administratively in the RPP. In its implementation, the teachers’ participation was actively involved in the realization of 100 percent activities with ethnopedagogical-based RPP output